Online Course Registration and Advisory Systems Based on Students’ Personal and Social Constraints - Faraj, Bamo Nadir; Muhammed, Aree Ali (Kurdistan Journal of Applied Research, 2021)
Komar University of Science and Technology (KUST) is among very few universities in Iraq that follows the prerequisite system which is very common in the tertiary level institutions around the world. In such kinds of systems, the prerequisites represent a one or set of courses a student must have completed in order to be able to enrol on a specific course. Although these kinds of systems give total freedom to students on when and how they are going to take courses, deciding which course to take that serves in the best interest of the student is very challenging and sometimes time consuming.This paper presents a web based system developed and implemented by KUST facilitating course registration for the students and administrative staff such that the best possible schedule and course/section combination is presented to the students considering their personal constraints and course requirements. To assist students to make proper decisions the system provides them with collected and analyzed historical data about each offered course such as passing rate of the course, the number of selected friends who registered for and marked the course as favorite and how many courses the selected course is prerequisite of. The collected data is gathered from the currently in place database containing course registration data since spring 2016 which is believed to be adequate to produce accurate results.The system also has the role of academic advisor, which plays an important role in the students’ academic life. Since traditional advising requires extra effort, times and sometimes the suggestion that comes from an academic advisor might not be in the best interest of students due to the lack of information about the student’s academic background or not having sufficient time advising a large number of students in a short window of registration period.